Workshop Ecoprint Berbasis Bahan Alam sebagai Upaya Meningkatkan Kreativitas dan Keterampilan Motorik Halus Anak di Desa Cisampih - Okta Fitriani; Didin Budiman (CV. SINAR HOWUHOWU, 2026)
This community service program aimed to improve children's creativity and fine motor skills through an ecoprint workshop using natural materials in Dusun Cisampih Jatigede District Sumedang Regency. The activity was designed as participatory training consisting of preparation socialization demonstration practice mentoring and evaluation. Participants were 19 elementary and junior high school students from Dusun Cisampih. Data were obtained through observation of participant involvement assessment of the ecoprint products and question and answer sessions after the workshop. The activity was implemented smoothly and participants showed good enthusiasm throughout the program. Most participants were able to understand the instructions and complete each stage of the ecoprint process independently with guidance from the facilitators. The workshop encouraged creativity through motif design and discussion of product utilization while also improving fine motor skills through activities requiring accuracy patience and hand eye coordination. Group based implementation and intensive mentoring supported the learning process and helped maintain participant engagement. Overall the ecoprint workshop proved to be an effective educational activity that utilized local natural resources while fostering creativity fine motor development and environmental awareness among children.